Climate risk assessment of the Tangier-Tetouan-Al Hoceima coastal Region (Morocco) - Agharroud, Kamal; Puddu, Manuela; Ivčević, Ante; Satta, Alessio; Kolker, Alexander S.; Snoussi, Maria (Frontiers in Marine Science, 2023)
Coastal zones occupy a prominent position in the sustainable management perspective of Tangier-Tetouan-Al Hoceima (TTA) region because they accommodate a majority of the region’s population and contribute to the economic wellbeing of local communities. High demographic and economic pressures associated to climatic and environmental factors increase and intensify the vulnerability of these coastal areas. The latter are severely affected by climate change implications in the course of time, which lead to damage and loss in coastal low-lying zones. In practice, the risks related to climate change, as coastal risks, are frequently addressed, and assessing coastal risk in the context of climate change is a research priority. The aim of this work is to evaluate the flooding risk of TTA coasts, taking into account the inundation level related to the conditions of extreme wave (return period of 100-year) and extreme sea level rise. We firstly defined the coastal hazard zone that corresponds to the maximum inundation level of 13 m for the whole area. We then applied a Coastal Risk Index application at the Local Scale (CRI-LS) methodology to calculate forcing, vulnerability, exposure and risk indices using nineteen physical, environmental and socioeconomical variables. Findings show that coastal hazard zone of Tangier-Tetouan-Al Hoceima region is extremely exposed to coastal forcing. More than 50% of the hazard zones indicates highly vulnerable zones and highest exposure is generally focused on the most populated urban zones. In the light of this, the coastal risk mapping shows hotspot zones in terms of climate change-related coastal risks located at Tangier Bay, south of Tangier city, Fnideq and Martil coasts, Tetouan city and north of Ksar El Kbir city. This paper corresponds to a useful support that can help policy-makers in decision-making to quietly follow coastal planning and management processes and participate in preserving coastal areas for future generations, which support the sustainable development goals of Agenda 2030 started by the United Nations with the goal of eradicating all kinds of poverty.